Human leukocyte antigen evolutionary divergence as a novel risk factor for donor selection in acute lymphoblastic leukemia patients undergoing haploidentical hematopoietic stem cell transplantation - Cao, Xing-Yu; Zhou, Hai-Fei; Liu, Xiang-Jun; Li, Xiao-Bo (Frontiers in Immunology, 2024)
The human leukocyte antigen (HLA) evolutionary divergence (HED) reflects immunopeptidome diversity and has been shown to predict the response of tumors to immunotherapy. Its impact on allogeneic hematopoietic stem cell transplantation (HSCT) is controversial in different studies. In this study, we retrospectively analyzed the clinical impact of class I and II HED in 225 acute lymphoblastic leukemia patients undergoing HSCT from related haploidentical donors. The HED for recipient, donor, and donor-recipient pair was calculated based on Grantham distance, which accounts for variations in the composition, polarity, and volume of each amino acid within the peptide-binding groove of two HLA alleles. The median value of HED scores was used as a cut-off to stratify patients with high or low HED. The class I HED for recipient (R_HED class I ) showed the strongest association with cumulative incidence of relapse (12.2 vs. 25.0%, P = 0.00814) but not with acute graft-versus-host disease.The patients with high class II HED for donor-recipient (D/R_HED class II ) showed a significantly higher cumulative incidence of severe aGVHD than those with low D/R_HED class II (24.0% vs. 6.1%, P = 0.0027). Multivariate analysis indicated that a high D/R_HED class II was an independent risk factor for the development of severe aGVHD (P = 0.007), and a high R_HED class I had a more than two-fold reduced risk of relapse (P = 0.028). However, there was no discernible difference in overall survival (OS) or disease-free survival (DFS) for patients with high or low HED, which was inconsistent with the previous investigation. While the observation are limited by the presented single center retrospective cohort, the results show that HED has poor prognostic value in OS or DFS, as well as the associations with relapse and aGVHD.In haploidentical setting, class II HED for donor-recipient pair (D/R_HED class II ) is an independent and novel risk factor for finding the best haploidentical donor, which could potentially influence clinical practice if verified in larger cohorts.